Analysis of Lead (Pb) Heavy Metal Content in Tengkuyung Snail (Cerithidea obtuse) and Sediment in the Kuala Mangrove Area of Singkawang City - Rafdinal Rafdinal; Riza Linda; Gusti eva Tavita; Bambang Kurniadi; Anthoni B Aritonang (Jurnal Biologi Tropis, 2022)
Tengkuyung (Cerithidea obtuse) is one of the many snails that live in mangrove areas, being a source of food and the economy, especially for people in coastal areas. Land and sea development and transportation activities have the potential to become a source of Pb contamination in tengkuyung and its environment. This study aims to determine the concentration of lead metal (Pb) in sediments and tengkuyung in the Kuala mangrove area of Singkawang City. Sampling was carried out at two station points. Measurement of heavy metal lead (Pb) in sediments and tengkuyung was carried out using atomic absorption spectrophotometry (SAA) method. The results showed that the content of lead (Pb) in the sediment and tengkuyung at station 1 was 0.0914 µg/g and <0.0070 (µg/g), while at station 2 it was 0.3927 µg/g and <0.0070 (µg/g). The content of Pb metal in tengkuyung meat still meets the eligibility for consumption because it is below the threshold according to SNI no. 7387 in 2009, which is 0.5 mg/kg (0.5 ppm).